2005
DOI: 10.1590/s0102-79722005000300002
|View full text |Cite
|
Sign up to set email alerts
|

Linguagem e cognição na doença de Alzheimer

Abstract: Mudanças na pirâmide populacional, mostrando o aumento do número de idosos indicam a necessidade de se diagnosticar, prevenir e tratar causas de comprometimento cognitivo prevalentes no envelhecimento, que comprometem a independência e inserção social desses indivíduos. O primeiro passo nesse sentido é compreender sinais e sintomas, nos seus aspectos neurobiológicos e comportamentais e, no que diz respeito à linguagem, sua interação com outros declínios na esfera cognitiva. Nosso objetivo é revisar a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
31

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 29 publications
4
23
0
31
Order By: Relevance
“…The evaluated elderly showed no change in verbal production in relation to the phonetic-phonological level, which corroborates the literature 13 which states that language difficulties resulting from dementia (particularly Alzheimer's) rarely include phonetic-phonological aspects in language production. However, the same authors reported also on the phonetic-phonological aspects -now about understanding -that subjects with dementia can present inability to synthesize and process the information provided by speech, which meets this study, in which the elderly presented difficulties in auditory processing tests that assess these skills, as will be discussed below.…”
Section: Discussionsupporting
confidence: 88%
“…The evaluated elderly showed no change in verbal production in relation to the phonetic-phonological level, which corroborates the literature 13 which states that language difficulties resulting from dementia (particularly Alzheimer's) rarely include phonetic-phonological aspects in language production. However, the same authors reported also on the phonetic-phonological aspects -now about understanding -that subjects with dementia can present inability to synthesize and process the information provided by speech, which meets this study, in which the elderly presented difficulties in auditory processing tests that assess these skills, as will be discussed below.…”
Section: Discussionsupporting
confidence: 88%
“…The maintenance of linguistic and communicative abilities in the elderly is correlated with the preservation of cognitive functions [17][18][19] . In advanced stages of cognitive impairment, patients may have a mean reduction in specific aspects of communication, such as initiative, spontaneity and speech recognition, even though they may still have some ability to communicate and to adapt to their environment 20 . Other studies have reported that aspects such as attention and working memory (phonological loop) would be particularly affected in patients with language impairments, especially oral comprehension, defined as the ability to process and manipulate information received through speech [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…As alterações fonoaudiológicas estão inicialmente associadas a dificuldades na comunicação, evoluindo progressivamente para níveis mais elevados de dependência de uma forma geral, incluindo as atividades de vida diária, especialmente a alimentação, com dificuldade marcante na mastigação e deglutição. O doente torna-se totalmente dependente, especialmente para atividades de vida diária, alimentação e higiene pessoal 5 , o que deteriora completamente sua qualidade de vida. Apesar da caracterização específica de cada estágio, a evolução clínica da doença, bem como as alterações e dificuldades decorrentes, são únicas para cada indivíduo 6 .…”
Section: Métodounclassified